Análise do comportamento e crescimento do camarão branco Litopenaeus vannamei (Boone, 1931) em diferentes substratos inconsolidados - Santos, Daniele Bezerra dos (2007)
The aim of this study was to test the sediment preference of L. vannamei shrimp. It was observed shrimp visit frequency, swimming and burying behaviour at different sediment compositions for 24h. Juvenile (0.93 ± 0.29g) and sub-adult shrimps (10.0 ± 1.18g) were obtained from the aquaculture station at Universidade Federal Rural do Semi-Árido UFERSA, and held in a plastic tank (water volume 500 L) supplied with aerated water and kept at constant temperature, pH, and salinity. Shrimp was fed by commercial shrimp dry food. The experimental substrates were composed by A: medium sand + thick sand + very thick sand + gravel; B: very fine sand + fine sand; and C: silt + clay. Thus, six different substrate combinations were tested: A, B, C, A+B, A+C, B+C. To test preference, it was used a cylindrical tank (40 l) divided into six differently substrate compartments. A single shrimp was introduced each tank and the frequency at which this shrimp visited each compartment was recorded over a 24h study period. It was tested 54 shrimp (18 sub-adult males, 18 subadult females and 18 juveniles). For each trial, sediment and water were changed to avoid pheromones and residues influence. Shrimp were weighted and sub-adults were divided by sex: males present petasma and females present thelycum. Data were collected on the experimental day at 19:30; 20:30; 00:30; 1:30; 05:30; 06:30; 13:30 and 14:30 h. At each time point, shrimp were observed for 20-min periods, in which we noted down which compartment the shrimp was occupying at 2-min intervals. Thus, for each period we had eleven observations (88 observations per day). For observations at night, it was used dim red light that did not affect shrimp behaviour. At each 20-min period, it was observed visit frequency in each substrate, if shrimp was burred or not or if it was swimming. There was not significant difference between light and dark burry activity for females. Swimming activity was significantly higher at night, mainly at 00:30 and 01:30 h. All L. vannamei shrimp showed preference for sediment B. This animal presents cyclic activity, spends the day light period buried and swims at night